ANALYSIS IMPLEMENTATION BASED ON PSAK 109 ACCOUNTING ZAKAT, INFAQ, SADAQAH IN LAZ YATIM MANDIRI PONOROGO - Eva Noor Fitriyani (UNIB Press, 2023)
This study aims to analyze the implementation of accounting for zakat, infaq, and sadaqah based on PSAK 109 contained in the Amil Zakat Yatim Mandiri Ponorogo as one of the OPZs in Ponorogo. This research uses data collection methods observation, documentation, and interviews, through a qualitative-descriptive approach. The data collection method in this study was through interviews informant of Yatim Mandiri Ponorogo to obtain information related to analyze implementation of PSAK 109. The validity test of the data using triangulation techniques. As well as documentation to support credibility in conducting the observation process and interviews conducted by researcher. The application of accounting treatment in the variables of presentation of financial statement in LAZ Yatim Mandiri has been carried out separately which means following the rules of PSAK 109. The implementation of accounting treatment in the disclosure variables for the management of ZIS fund is not following PSAK 109 because LAZ Yatim Mandiri has not yet elaborated CaLK. This research is expected to provide development for LAZ Yatim Mandiri Ponorogo and other LAZs to apply accounting ZIS based on PSAK 109 as a whole.